Evaluation of Probiotic and Antidiabetic Attributes of Lactobacillus Strains Isolated From Fermented Beetroot - Kumari, V. B. Chandana; Huligere, Sujay S.; Ramu, Ramith; Naik Bajpe, Shrisha; Sreenivasa, M. Y.; Silina, Ekaterina; Stupin, Victor; Achar, Raghu Ram (Frontiers in Microbiology, 2022)
Fermented foods are sources of functionally salient microbes. These microbes when ingested can regulate biomolecule metabolism which has plethora of health benefits. Lactic acid bacteria species (LABs) isolates from fermented beetroot was biochemically characterised & validated using 16s rRNA sequence. Also, an in-vitro assay was conducted to confirm probiotic activity of isolates. The cell-free supernatant (CS), cell-free extract (CE) and intact cell (IC) were evaluated for α-glucosidase and α-amylase inhibition. Six isolates RAMULAB01-06 were categorised to be Lactobacillus spp. by observing phenotypic and biochemical characters. Molecular validation by using 16S rDNA sequencing, followed by homology search in NCBI database suggested the isolates are to be >95% similar to L. paracasei and L. casei. Also, isolates exhibited the probiotic potential with high survival rate (> 96%) in gastro intestinal condition, and adherence capability (> 53%), colonization (> 86%), antibacterial, and antibiotic activity. The safety assessments expressed the isolates recognised to be safe. The α-glucosidase and α-amylase inhibition of CS, CE and IC ranged from 3.97±1.42 % to 53.91±3.11%, 5.1±0.08% to 57.15±0.56% respectively. Hence these species have exceptional antidiabetic potential which could be explicated to its use as functional food and health-related food products.